Improved mother's health helps in universalisation of child immunisation – myth or reality? Evidence from Assam. Issue 6 (18th August 2021) - Maity, Shrabanti; Barlaskar, Ummey Rummana; Bhumali, Anil
ABSTRACT: The study aims to inspect the child immunisation status of Barak Valley, Assam. Simultaneously, the study scrutinises the efficacy of the mother's health status along with other social, economic and demographic factors on universalising child's immunisation in the study area holistically. The study is based on a novel data set especially collected for this study. The study exercises the Multiple Correspondence Analysis and Logit model for investigating the objectives. It concludes that other than the mother's health status, mother's education, religion, the sex of the child, etc., are important decisive components of child immunisation in the study area.